Adaptive feedforward control of closed orbit distortion caused by fast helicity‐switching undulators. (21st October 2021) - Masaki, Mitsuhiro; Maesaka, Hirokazu; Soutome, Kouichi; Takano, Shiro; Watanabe, Takahiro; Kubota, Kouji; Fujita, Takahiro; Dewa, Hideki; Fukui, Toru; Sugimoto, Takashi; Takeuchi, Masao; Tanaka, Hitoshi
Abstract : A new orbit correction scheme based on the adaptive feedforward control (AFC) is presented. The developed AFC technique provides a new option in orbit control for light source stabilization at synchrotron radiation facilities. Abstract : A new correction algorithm for closed orbit distortion based on an adaptive feedforward control (AFC) has been developed. At SPring‐8, two helicity‐switching twin‐helical undulators (THUs) had been implemented with conventional feedforward corrections. However, the validity of these corrections turned out to be expiring due to unforeseen variation in the error magnetic fields with time. The developed AFC system has been applied to the THUs dynamically updating the feedforward table without stopping the helicity switching amid user experiments. The error sources in the two THUs are successfully resolved and corrected even while the two THUs are switching simultaneously with the same repetition period. The actual operation of the new AFC system enables us to keep the orbit variations suppressed with an accuracy at the sub‐micrometre level in a transparent way for light source users.